Modern control engineering - Singh, Yaduvir; Janardhanan, S. ([S.l.] : Cengage Learning Asia, 2011)
Modern Control Engineering is primarily designed to serve as a textbook for undergraduate students of engineering for a course on Control Systems. The book has been carefully developed to cover all topics that are essential to develop an understanding of control systems. Beginning with the study of basics of control systems, the book proceeds to provide a comprehensive coverage of important concepts such as Lorentz transforms and z-transforms; transfer function and gain; block diagrams and signal flow graphs; time-domain modeling; analogous systems and physical system modeling; control system components; time response analysis of control systems and error criterion; stability analysis; controllers; compensation in control systems; eigenvalues and eigenvectors; and industrial control systems. Written in a student-friendly manner, the book contains a large number of solved examples to provide a good and clear understanding of the concepts discussed. Figures and tables interspersed throughout the book successfully supplement the text. Solved problems and unsolved exercises have been included at the end of each chapter to test students knowledge regarding the topics covered therein. KEY FEATURES (1) Extensively covers several important concepts related to control systems (2) Contains a large number of solved examples (3) Includes figures and tables that add to the utility of the text (4) Contains solved problems and unsolved exercises at the end of each chapter.